2022
DOI: 10.1186/s12968-022-00903-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the findings and diagnostic sensitivity of cardiovascular magnetic resonance in biopsy confirmed acute myocarditis with infarct-like vs. heart failure presentation

Abstract: Background Cardiovascular magnetic resonance (CMR) is considered the reference imaging modality in providing a non-invasive diagnosis of acute myocarditis (AM), as it allows for the detection of myocardial injury associated with AM. However, the diagnostic sensitivity and pattern of CMR findings appear to differ according to clinical presentation. Methods This is a retrospective cross-sectional study. Consecutive adult patients presenting to a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This mechanism is also able to justify, in part, the different locations of the signal alterations found in the two study samples; the "non-infarct-like" form showed, in our study, a significantly greater distribution of edema (p = 0.0308) and a significantly greater extent of edema and LGE at the level of the lateral (p = 0.0405 and p = 6.91 × 10 −4 , respectively) and inferior segments (edema p = 0.045) of the LV, particularly in the midsegment (p = 0.0076). The infero-lateral middle (basal) wall of the LV is, in fact, described as the site commonly affected by the phlogistic process, and it is the one in direct contact with the pericardium, accounting for its frequent involvement in AM caused by cardiotropic viruses (PVB19), as mentioned previously [2,5,12,21,25,26]. This localization of tissue damage in relation to PVB19 infection was described by Mahrholdt et al in association with an "infarct-like" presentation of AM [19].…”
Section: Tissue Characterization Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…This mechanism is also able to justify, in part, the different locations of the signal alterations found in the two study samples; the "non-infarct-like" form showed, in our study, a significantly greater distribution of edema (p = 0.0308) and a significantly greater extent of edema and LGE at the level of the lateral (p = 0.0405 and p = 6.91 × 10 −4 , respectively) and inferior segments (edema p = 0.045) of the LV, particularly in the midsegment (p = 0.0076). The infero-lateral middle (basal) wall of the LV is, in fact, described as the site commonly affected by the phlogistic process, and it is the one in direct contact with the pericardium, accounting for its frequent involvement in AM caused by cardiotropic viruses (PVB19), as mentioned previously [2,5,12,21,25,26]. This localization of tissue damage in relation to PVB19 infection was described by Mahrholdt et al in association with an "infarct-like" presentation of AM [19].…”
Section: Tissue Characterization Parametersmentioning
confidence: 93%
“…The sample size of the study is small, reflecting the activity of a single hospital center; however, it is of the order of magnitude overlapping with that of some recent studies [1,15,25]. The CMR diagnosis was confirmed by clinical diagnosis in all enrolled patients, however, without biopsy.…”
Section: Study Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is based on the Lake Louise Criteria (LLC) including T1 and T2 mapping and has been shown to assess severe inflammation and fibrosis [15]. However, the diagnostic power of CMR is limited because CMR is unable to detect the underlying etiology of myocarditis, particularly the presence of viral infections and transcriptional activity and the quality and intensity of inflammation cannot be accurately detected [11,16,17]. Therefore, no therapeutic decision can be made based on imaging alone [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the substantial role of non-invasive cardiac magnetic resonance imaging (CMRI), which is the reference standard for diagnosis, bypassing the risks associated with cardiac biopsies. With the use of cardiac MRIs, regions of myocarditis have been observed to closely correlate with regions of abnormal signal [13][14][15][16]. The current recommendations are proposed on the basis of consensus emerging from the position statement that invasive studies such as endomyocardial biopsies (EMBs) should be performed only if there is a good overall prognosis for patients with mild acute dilated cardiomyopathy, even if these subjects are potentially at risk of worsening clinical conditions.…”
mentioning
confidence: 99%